(untitled) - Julene, Fischer (Boston, Massachusetts, 1986)
The image of the VietNma War is a shattered mirror. The VietNma War was the most thoroughly photographed combat in history. The camera's eye recorded it all-a GI sobbing over a dead bubby, a naked Vietnamese child fleeing a napalm attack, a Budhhist monk being consumed by flames, an American President brooding over events that have broken from his control, the joyous return of a hero from a Hanoi prison, the grisly sight of villagers slain by Vietcong guerrillas. Words too have te power to evoke images. Such words as courage, sacrifice, brotherhood, tenacuty, words that time and again found their application to men on both sides of the fighting. Or otehr words that buzz ominously in memory like insects. Body count. Pacification. Tonkin Gulf. Kent State. Boat people. "Hell, no! We won't go!" Pol Pot. The prison called Hanoi Hilton with its torture rooms. The bloodieed highway ironically called the Street of Joy
Keywords: Vietnam conflict,Việt Nam; Lịch sử; 1961-1975